Hungarian Monitoring, 27 January 1990 . [Magyar rádiófigyelő], 1990. január 27 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Changes in the Romanian education ministry - Situation normalizes in Baku - Trials start in Bucharest - Polish United Workers' Party's last congress convenes - Armenia: ceasefire agreement Domestic Affairs: - Havel's visit to Budapest - Second round of Hungarian Socialist Workers' Party (MSZMP) congress - Hungarian Socialist Party (MSZP) on Soviet troop withdrawals - Phone tapping scandal - Women in Soviet labor camps - Alliance of Democratic Youth (DEMISZ) holds its 2nd national congress - Gabčíkovo-Nagymaros dam Economy: - Parties' economic experts on the need for cooperation Külpolitika: - Változás a román oktatási minisztériumban - Normalizálódik a helyzet Bakuban - Bukarestben megkezdődött a négyek pere - Ülésezik a LEMP utolsó kongresszusa - Örményország: fegyverszüneti szerződés Belpolitika: - Havel budapesti látogatása - MSZMP kongresszus 2-ik fordulója - Az MSZP a szovjet csapatkivonásról - Lehallgatási botrány - Asszonyok szovjet közmunkatáborokban - DEMISZ 2. országos kongresszusa - Bős-Nagymarosi vízlépcső ügy Gazdaság: - Pártok gazdasági szakértői az együttműködés szükségességéről